Butte Paper - Determination of Gases in Smelter Flues; and Notes on the Determination of Dust Losses at the Washoe Reduction Works, Anaconda, Mont. - Edgar M. Dunn (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1914)
Part I. Determination oF Gases in Smelter Flues. General considerations. Regular methods for carbon monoxide, oxygen, nitrogen, moisture. Sulphur oxides-—Methods of Lunge and Hempel tried, and either modified or discarded, with reasons therefor. Gravimetric method developed at Anaconda. Description of apparatus used. Brief notes on Richter and Hawley methods for the direct cietermination of sulphur trioxide. Carbon dioxide, with complete notes on same. Arsenic trioxide. Table of percentages of flue gas constituents found at a Western smelter. Some final notations as to the value of flue gas analysis, in connection with an intelligent log of furnace operations. Part II. Notes on the Determination oF Dust Losses at the Washoe Reduction Works, Anaconda, Mont. Discussion of problem, with description of flue system. Various places and methods for determinations of velocity. Instruments used. Procedure in making determinations for velocity. Soundings of cross-section for depths of dust. Calculation of velocities and areas. Daily volume of gas, and plant operations during tests. Place for dust determinations. Apparatus and methods of 'sampling. Results obtained, with table of daily amount of dust losses. Analysis of dusts for values, from various sampling stations. Complete analysis of composite sample of stack emanation. Last analysis totaled to show form in which present. Discussion of recovery as a commercial proposition. References on Pitot tube and calculations.